2020
DOI: 10.1136/bcr-2020-236692
|View full text |Cite
|
Sign up to set email alerts
|

Serial anterior segment optical coherence tomography post autologous simple limbal epithelial transplantation

Abstract: A 24-year-old young man presented to us with total limbal stem cell deficiency (LSCD) in the right eye 1 year post ocular chemical burn. The patient subsequently underwent limbal biopsy in the healthy contralateral eye and autologous simple limbal epithelial transplantation in the right eye. The patient was followed up with sequential imaging of the cornea with high-resolution anterior segment optical coherence tomography (HR-ASOCT) for 3 years. The serial HR-ASOCT imaging in the operated eye showed regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The possible explanation for this could be that limbal biopsies contain mesenchymal stromal cells in addition to LESCs which may be responsible for reducing corneal scarring in these eyes. 27 In studies on the reflectivity patterns of corneal stroma post-SLET, Kate et al 28,29 found that the changes of stromal remodeling continued until the 1year follow-up period of the study. This could obviate or delay the need for keratoplasty, and in this period, a CL trial should be offered.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation for this could be that limbal biopsies contain mesenchymal stromal cells in addition to LESCs which may be responsible for reducing corneal scarring in these eyes. 27 In studies on the reflectivity patterns of corneal stroma post-SLET, Kate et al 28,29 found that the changes of stromal remodeling continued until the 1year follow-up period of the study. This could obviate or delay the need for keratoplasty, and in this period, a CL trial should be offered.…”
Section: Discussionmentioning
confidence: 99%